Pengaruh Dukungan Edukatif Ibu Dalam Pembelajaran Terhadap Pengelolaan Emosi Akademik Mahasiswa - Atikha, Oktiyani Devi; Kuswardinah, Asih (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2026)
This study was conducted to examine the influence of maternal educational support on students’ academic emotional regulation, with the aim of determining the extent of this influence. The study employed a quantitative method using a survey technique involving 101 students as research subjects. Data were collected via a questionnaire measuring maternal educational support and students’ academic emotional regulation. Data analysis was conducted using simple linear regressionwith the aid of SPSS software. The findings of this study reveal that a mother’s educational support has a significant effect on students’ academic emotional regulation (p 0.001). The coefficient of determination (R = 0.194) indicates that mothers’ educational support contributes 19.4% to students’ ability to manage academic emotions. These findings suggest that the higher the level of educationalsupport provided by mothers, the better students’ ability to regulate emotions related to academic activities.